2023
DOI: 10.1088/1361-6528/ace193
|View full text |Cite
|
Sign up to set email alerts
|

Capacitively coupled nonthermal plasma synthesis of aluminum nanocrystals for enhanced yield and size control

Abstract: Uniform-size, non-native oxide-passivated metallic aluminum nanoparticles (Al NPs) have desirable properties for fuel applications, battery components, plasmonics, and hydrogen catalysis. Nonthermal plasma-assisted synthesis of Al NPs was previously achieved with an inductively coupled plasma (ICP) reactor, but the low production rate and limited tunability of particle size were key barriers to the applications of this material. This work focuses on the application of capacitively coupled plasma (CCP) to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Plasmas, as a highly energetic and rapid gas-phase synthesis technique, are paving the way for sustainable, fully electric, and solvent-free synthesis of a variety of functional nanomaterials. Despite extensive research on their applications in elemental and compound semiconductor nanomaterials production [20][21][22][23], few studies have been reported that explore the potential of plasmas for metal nanoparticle syntheses [24][25][26]. Theoretical calculations showed that an atmospheric-pressure thermal plasma with mixture of Ar, H 2 , and TiCl 4 is a feasible route for the production of titanium nanoparticles [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmas, as a highly energetic and rapid gas-phase synthesis technique, are paving the way for sustainable, fully electric, and solvent-free synthesis of a variety of functional nanomaterials. Despite extensive research on their applications in elemental and compound semiconductor nanomaterials production [20][21][22][23], few studies have been reported that explore the potential of plasmas for metal nanoparticle syntheses [24][25][26]. Theoretical calculations showed that an atmospheric-pressure thermal plasma with mixture of Ar, H 2 , and TiCl 4 is a feasible route for the production of titanium nanoparticles [27,28].…”
Section: Introductionmentioning
confidence: 99%